2018
DOI: 10.1186/s12879-018-3017-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a vaccination programme in children vaccinated with ProQuad, and ProQuad-specific effectiveness against varicella in the Veneto region of Italy

Abstract: BackgroundMonovalent varicella vaccines have been available in the Veneto Region of Italy since 2004. In 2006, a single vaccine dose was added to the immunisation calendar for children aged 14 months. ProQuad®, a quadrivalent measles-mumps-rubella-varicella vaccine, was introduced in May 2007 and used, among other varicella vaccines, until October 2008. This study aimed to evaluate the effectiveness of a single dose of ProQuad, and the population impact of a vaccination program (VP) against varicella of any se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…Notably, in Hungary, UVV was introduced in 2019, shortly before the COVID-19 pandemic began, limiting the period of observation to evaluate the effect of UVV under pre-pandemic conditions. This aside, our findings accord with studies from Europe and the United States reporting declines in varicella infections and hospitalization in the years following UVV implementation [ 6 , 7 , 25 , 32 ]. For example, in Germany UVV led to a greater than 50% reduction in varicella cases and a greater than 70% reduction in varicella-associated hospitalizations [ 7 ], while in Veneto, Italy, incident varicella in children fell by 90% following the introduction of a quadrivalent measles-mumps-rubella-varicella vaccine [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, in Hungary, UVV was introduced in 2019, shortly before the COVID-19 pandemic began, limiting the period of observation to evaluate the effect of UVV under pre-pandemic conditions. This aside, our findings accord with studies from Europe and the United States reporting declines in varicella infections and hospitalization in the years following UVV implementation [ 6 , 7 , 25 , 32 ]. For example, in Germany UVV led to a greater than 50% reduction in varicella cases and a greater than 70% reduction in varicella-associated hospitalizations [ 7 ], while in Veneto, Italy, incident varicella in children fell by 90% following the introduction of a quadrivalent measles-mumps-rubella-varicella vaccine [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Since 1974, vaccines (containing Leningrad-3 strain) have been used in the former Soviet Union. It is estimated that 8-11 million doses of the Leningrad-3 mumps vaccine is produced every year [78]. There was a study to explore the seroconversion rates after vaccination with an MMR vaccine (measles vaccine with the Leningrad-16 strain, mumps vaccine with the Leningrad-3 strain, and rubella virus vaccine with the Leningrad-8 strain) [100].…”
Section: Leningrad-3 Strain Mumps Vaccinementioning
confidence: 99%
“…The Biken Institute in Japan developed the Urabe Am9 strain vaccine from mumps virus isolated from the saliva of a patient in 1979, and thereafter, the vaccine was licensed in Belgium, France, Italy, and many countries worldwide [76,78].…”
Section: Urabe Strain Mumps Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…23,38,40 In addition, results of this model are consistent with real-world observational studies showing the impact of UVV in countries such as Italy and the United States. [41][42][43] Comparing the economic impact of vaccination between countries can be challenging given the heterogeneity in varicella infection reporting and differences in health care systems and vaccine pricing across countries. Nonetheless, the similarity of results between this modeling study and those previously reported highlights the financial benefit of varicella vaccination from both payer and societal perspectives.…”
Section: Discussionmentioning
confidence: 99%